Blood transfusion improves renal oxygenation and renal function in sepsis-induced acute kidney injury in rats. Issue 1 (December 2016) - Zafrani, Lara; Ergin, Bulent; Kapucu, Aysegul; Ince, Can
Abstract Background The effects of blood transfusion on renal microcirculation during sepsis are unknown. This study aimed to investigate the effect of blood transfusion on renal microvascular oxygenation and renal function during sepsis-induced acute kidney injury. Methods Twenty-seven Wistar albino rats were randomized into four groups: a sham group (n  = 6), a lipopolysaccharide (LPS) group (n  = 7), a LPS group that received fluid resuscitation (n  = 7), and a LPS group that received blood transfusion (n  = 7). The mean arterial blood pressure, renal blood flow, and renal microvascular oxygenation within the kidney cortex were recorded. Acute kidney injury was assessed using the serum creatinine levels, metabolic cost, and histopathological lesions. Nitrosative stress (expression of endothelial (eNOS) and inducible nitric oxide synthase (iNOS)) within the kidney was assessed by immunohistochemistry. Hemoglobin levels, pH, serum lactate levels, and liver enzymes were measured. Results Fluid resuscitation and blood transfusion both significantly improved the mean arterial pressure and renal blood flow after LPS infusion. Renal microvascular oxygenation, serum creatinine levels, and tubular damage significantly improved in the LPS group that received blood transfusion compared to the group that received fluids. Moreover, the renal expression of eNOS was markedly suppressed under endotoxin challenge. Blood transfusion, but not fluid resuscitation, was able to restore the renal expression of eNOS. However, there were no significant differences in lactic acidosis or liver function between the two groups. Conclusions Blood transfusion significantly improved renal function in endotoxemic rats. The specific beneficial effect of blood transfusion on the kidney could have been mediated in part by the improvements in renal microvascular oxygenation and sepsis-induced endothelial dysfunction via the restoration of eNOS expression within the kidney.